2013
DOI: 10.1002/lary.24011
|View full text |Cite
|
Sign up to set email alerts
|

Can pillar suturing promote efficacy of adenotonsillectomy for pediatric osas? A prospective randomized controlled trial

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Furthermore, previous studies that indicate that APP is more effective than ATE are not convincing. For instance, in the small prospective study from Chiu et al 126 (n = 24), the groups were not randomized and not similar at baseline, which could explain the better effect after APP. Nevertheless, while Friedman et al 125 (n = 60) conducted an RCT and have suggested there might be a difference between APP and ATE, their results were not statistically significant.…”
Section: Papers II and Iii -Is Adenopharyngoplasty Better Than Adenotmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, previous studies that indicate that APP is more effective than ATE are not convincing. For instance, in the small prospective study from Chiu et al 126 (n = 24), the groups were not randomized and not similar at baseline, which could explain the better effect after APP. Nevertheless, while Friedman et al 125 (n = 60) conducted an RCT and have suggested there might be a difference between APP and ATE, their results were not statistically significant.…”
Section: Papers II and Iii -Is Adenopharyngoplasty Better Than Adenotmentioning
confidence: 99%
“…While the results from that study were in favor of APP, no significant group differences were observed, and the authors reported that the study was underpowered due to a high dropout rate (27%). Further, a non-randomized prospective controlled study by Chiu et al 126 in 2013 showed that APP (n = 12) was significantly more effective than ATE (n = 12), with a reduction in apnea-hypopnea index (AHI) of 80% compared to 43%. These studies indicate that APP might be a more effective surgical method than ATE, but the overall evidence is weak.…”
Section: Adenotonsillectomy and Adenopharyngoplastymentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has several limitations: although the same anesthesia procedure was applied to every child to minimize potential influences of postoperative analgesics on cognitive abilities, we could not definitely distinguish the effects of anesthesia itself from other confounders associated with anesthesia. First, although we excluded surgeries (such as operations to treat obstructive sleep apnea syndrome [ 23 ] or nasosinusitis [ 24 ], urological and hepatorenal surgeries) which might have influenced postoperative intelligence, and pediatric patients with undiagnosed neurological complications observed at the 1 year follow-up after an orthopedic operation, it was difficult to conclude unequivocally it was the general anesthesia rather than the surgery per se that accounted for the change in intelligence [ 25 ], since patients might have experienced varying levels of stress due to surgical injury. Second, the lack of a standardized and valid methodology made it difficult to qualitatively and quantitatively evaluate childhood neurodevelopment in previous publications.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral pharyngoplasty involves suturing the anterior and posterior tonsillar pillars together to close the tonsillar fossa after tonsillectomy, leading to statistically significant AHI reduction, although not resolution of OSA. 39,40 In expansion pharyngoplasty, the palatopharyngeus muscle is anteriorly rotated and suspended on the soft palate after tonsillectomy, leading to statistically significant reduction of AHI in adults. 41 Modified expansion pharyngoplasty, involving tonsillectomy followed by dividing the superficial fibers of the palatopharyngeus and tunneling them upward into the palate, shows a greater cure rate for OSA than adenotonsillectomy alone.…”
Section: Patient Selection and Evaluationmentioning
confidence: 99%